Heterogeneous selective hydrogenation of ethylene carbonate to methanol and ethylene glycol over a copper chromite nanocatalyst. Issue 7 (4th December 2014) - Lian, Chao; Ren, Fumin; Liu, Yuxi; Zhao, Guofeng; Ji, Yongjun; Rong, Hongpan; Jia, Wei; Ma, Lei; Lu, Haiyuan; Wang, Dingsheng; Li, Yadong
Abstract : Heterogeneous selective hydrogenation of ethylene carbonate to methanol and ethylene glycol, which provides an opportunity for industrial application of CO2 indirect conversion, was achieved for the first time over a copper chromite nanocatalyst. Abstract : Heterogeneous selective hydrogenation of ethylene carbonate (EC), a key step in indirect conversion of CO2, was realized over a copper chromite nanocatalyst prepared via a hydrothermal method followed by calcination. The selectivities towards methanol (60%) and ethylene glycol (93%) were higher than those achieved over other usual hydrogenation catalysts.